Design of differentially-driven aperture-coupled microstrip antenna - Paul, Saw William Blessing. (2013)
Microstrip antennas have been one of the most innovative research fields in the design of antenna for the past three decades. It has many advantages such as light-weight, small-size, and can be matched to the host surface. Printed-circuit technology is used to produce these antennas with low cost for mass production. These antennas are replacing many conventional antennas.